(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Literary translation frequently involves bridging cultural gaps that extend well beyond direct linguistic equivalences. This article investigates the role of ethnocultural adaptation—here defined as the deliberate modification or contextualization of culturally specific elements to suit a new audience—in successful literary translation. Drawing on theoretical frameworks in Translation Studies (Baker, 2011; Munday, 2016) and empirical observations from comparative text analyses, this study examines how translators adapt culture-specific references to preserve both the semantic and aesthetic integrity of literary works. Through a combination of textual scrutiny, reader feedback, and cross-cultural comparisons, the research highlights key strategies (e.g., transliteration with footnotes, equivalent substitution, explicatory translation) and evaluates their effectiveness in maintaining cultural nuance. Results indicate that a balanced, context-sensitive approach to adaptation can enhance reader comprehension without sacrificing a text’s cultural authenticity. The discussion underscores the significance of ethnocultural awareness and suggests pathways for future research on how best to negotiate cultural identities in translation.